The effectiveness and cost-effectiveness of the Incredible Years® Teacher Classroom Management programme in primary school children: results of the STARS cluster randomised controlled trial. Issue 5 (18th July 2018) - Ford, Tamsin; Hayes, Rachel; Byford, Sarah; Edwards, Vanessa; Fletcher, Malcolm; Logan, Stuart; Norwich, Brahm; Pritchard, Will; Allen, Kate; Allwood, Matthew; Ganguli, Poushali; Grimes, Katie; et al.
Abstract: Background: We evaluated the effectiveness and cost-effectiveness of the Incredible Years ® Teacher Classroom Management (TCM) programme as a universal intervention, given schools' important influence on child mental health. Methods: A two-arm, pragmatic, parallel group, superiority, cluster randomised controlled trial recruited three cohorts of schools (clusters) between 2012 and 2014, randomising them to TCM (intervention) or Teaching As Usual (TAU-control). TCM was delivered to teachers in six whole-day sessions, spread over 6 months. Schools and teachers were not masked to allocation. The primary outcome was teacher-reported Strengths and Difficulties Questionnaire (SDQ) Total Difficulties score. Random effects linear regression and marginal logistic regression models using Generalised Estimating Equations were used to analyse the outcomes. Trial registration: ISRCTN84130388. Results: Eighty schools (2075 children) were enrolled; 40 (1037 children) to TCM and 40 (1038 children) to TAU. Outcome data were collected at 9, 18, and 30-months for 96, 89, and 85% of children, respectively. The intervention reduced the SDQ-Total Difficulties score at 9 months (mean (s.d. ):5.5 (5.4) in TCM v. 6.2 (6.2) in TAU; adjusted mean difference = −1.0; 95% CI−1.9 to −0.1; p = 0.03) but this did not persist at 18 or 30 months. Cost-effectiveness analysis suggested that TCM may be cost-effective compared with TAU at 30-months, but this result was associated with uncertainty so no firm conclusions can be drawn. A priori subgroup analyses suggested TCM is more effective for children with poor mental health. Conclusions: TCM provided a small, short-term improvement to children's mental health particularly for children who are already struggling.